Guidelines for the development and validation of patient-reported outcome measures: a scoping review - Jung, Andres; Challoumas, Dimitris; Pagels, Larissa; Armijo-Olivo, Susan; Braun, Tobias; Luedtke, Kerstin (BMJ Evidence-Based Medicine, 2024)
Objective The objectives of this scoping review were to provide an overview of existing guidelines for the development and validation of patient-reported outcome measures (PROMs), review them for comprehensiveness and clarity and provide recommendations for their use based on the goals of the instrument developers. Design Scoping review. Methods A literature search was performed in PubMed, Scopus, PsycInfo and Google Scholar up to 2 June 2023 to identify guidelines for the development and validation of PROMs. Screening of records and reports as well as data extraction were performed by two reviewers. To assess the comprehensiveness of the included guidelines, a mapping synthesis was performed and steps to develop and validate a measurement instrument outlined in the included guidelines were mapped to an a priori framework including 20 steps, which was based on the guideline by de Vet et al. Results A total of 40 guidelines were included. Statistical advice (at least partially) was provided in 98% of the guidelines (39/40) and 88% (35/40) of the guidelines included examples for steps required to develop and validate PROMs. However, 78% (31/40) of the guidelines were not comprehensive and two essential steps in PROM development (‘consideration and elaboration of the measurement model’ and ‘responsiveness’) were not included in 80% and 72% of the guidelines, respectively. Three guidelines included all 20 steps and six included almost all steps (≥90% of steps) for developing and validating a PROM. Discussion Most guidelines on PROM development and validation do not appear to be comprehensive, and some crucial steps are missing in most guidelines. Nevertheless, for some purposes of PROMs, many guidelines provide helpful advice and support. Conclusion At least 15 guidelines may be recommended, including three comprehensive guidelines that can be recommended for the development and validation of PROMs for most purposes (eg, to discriminate between subjects with a particular condition and subjects without that condition, to evaluate the effects of treatments (between a pre and post time-points) or to evaluate a status quo